Homeowner Subsidy Repeal and Housing Recentralization - Alexander Daminger; Kristof Dascher (ZBW - Leibniz Information Centre for Economics, 2021)
Subsidizing homeownership makes cities decentralize, so Muth (1967) suggested over half a century ago, and so Voith (1999) and Glaeser (2011) have argued more recently. This paper provides a first quasi-experimental test of "Muth's hypothesis". We analyze a homeownership subsidy's effects on urban form, by turning to Germany's 2005 subsidy repeal. Because housing in the city center was predominantly rental, prospective owner-occupiers needed to move to the city periphery. We are able to identify the subsidy's effect on decentralization because we capitalize on the subsidy's variation both in timing and design. We find that repealing the subsidy did contribute to recentralizing Germany's cities. This highlights the decentralizing role of the original homeownership subsidy. Inasmuch decentralization begets greater carbon dioxide emissions, encouraging homeownership is at cross-purposes with mitigating global warming.
Keywords: R12; D72; R52; 330; Homeownership Subsidy; Subsidy Repeal; Housing Recentralization; Global Warming; Suburban Land Use